2021
DOI: 10.1029/2020jb021598
|View full text |Cite
|
Sign up to set email alerts
|

Petrogenesis of Basaltic Lavas From the West Pacific Seamount Province: Geochemical and Sr‐Nd‐Pb‐Hf Isotopic Constraints

Abstract: The geochemical character of ocean island basalts (OIBs) produced by intraplate geodynamic mechanism indicates the mantle is heterogeneous. Courtillot et al. (2003) proposed that plume-related hotspots need to meet the following criteria: (i) the existence of linear volcanic chain with contiguous age progressions; (ii) the appearance of flood basalts in the initial site of volcanic track; (iii) enormous buoyant flux; (iv) high 3 He/ 4 He ratios of basalts; and (v) low shear wave velocity in the lower mantle. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 131 publications
(397 reference statements)
0
5
0
Order By: Relevance
“…Both the primitive-mantle-normalized distribution of trace elements and the normalized REE distribution of MP3D04, MP3D21, MP5D11, MP5D15A, MPID201, and MPID202 seamounts in the Western Pacific (Figures 5 and 6) exhibit similar patterns to those of OIB and are distinct from normal mid-ocean ridge basalts (N-MORB) and enriched ocean ridge basalts (E-MORB). OIB are generally considered to be the product of mantle plumes (hot spots) [19,36]. A comparison of trace element partitioning between the samples analyzed in this study with OIBs shows that the samples have been influenced by minor mixing with the crust, and the Nb/Yb versus Th/Yb diagram (Figure 7) also shows that the samples are not mixed with a large amount of circulating crustal components.…”
Section: Magma Sourcementioning
confidence: 80%
See 1 more Smart Citation
“…Both the primitive-mantle-normalized distribution of trace elements and the normalized REE distribution of MP3D04, MP3D21, MP5D11, MP5D15A, MPID201, and MPID202 seamounts in the Western Pacific (Figures 5 and 6) exhibit similar patterns to those of OIB and are distinct from normal mid-ocean ridge basalts (N-MORB) and enriched ocean ridge basalts (E-MORB). OIB are generally considered to be the product of mantle plumes (hot spots) [19,36]. A comparison of trace element partitioning between the samples analyzed in this study with OIBs shows that the samples have been influenced by minor mixing with the crust, and the Nb/Yb versus Th/Yb diagram (Figure 7) also shows that the samples are not mixed with a large amount of circulating crustal components.…”
Section: Magma Sourcementioning
confidence: 80%
“…Additionally, as a product of hot spot activity and related intraplate volcanism, seamounts represent the best direct evidence of intraplate magma activity in the lower mantle. The geochemical characteristics of provide important information about dynamic processes in the Earth, such as mantle magma source areas, which are key to better understanding how mantle processes determine the formation and evolution of seamounts and their resulting geochemical characteristics [11][12][13][14][15][16][17][18][19]. Moreover, seamounts contain a large variety of materials that constitute valuable seabed resources, such as cobalt-rich crusts.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments of multiple saturation points of the basalt with a mantle mineral assemblage provided the basis for understanding conditions of basaltic melt generation (Kushiro, 1972), and with an increasing number of theoretical and experimental studies thermodynamic modeling such as the Pmelts (Ghiorso et al., 2002), or geothermobarometric methods (e.g., Putirka, 2008) have also provided further insights. However, many case studies have shown that the source of basalt from various geological environments contributes to mafic source melts (e.g., Cheng et al., 2018; Howarth & Harris, 2017; Reid et al., 2017; Yan et al., 2021; Zhou et al., 2022). Experimental petrology studies have demonstrated that a diverse array of mafic and ultramafic rocks can generate basalt melts across a broad spectrum of temperature and pressure conditions, as highlighted by Kushiro (2001).…”
Section: Introductionmentioning
confidence: 99%
“…Constraining the source lithology of basalts provides insights into mantle metasomatism and/or crustal material recycling that contribute to mantle heterogeneity (e.g., Howarth & Harris, 2017; Reid et al., 2017; Ren et al., 2019; Xu et al., 2017; Yan et al., 2021; Zhou et al., 2022). The depth and temperature of basalt generation are in turn critical to our understanding of the thermal structure of the earth and how plate tectonics works, topics that are still intensively investigated and not well agreed upon (e.g., Green & Falloon, 2005; Herzberg, 2006; Niu & O'Hara, 2008; Lustrino et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Most of them are not directly associated with age-progressive hotspot tracks and are therefore difficult to explain within the classic mantle plume model [2][3][4][5][6][7]. They could be the result of shallow tectonically driven processes, and several models have been proposed (e.g., [8][9][10][11][12][13][14]), or alternatively the result of smaller scale mantle plumes (e.g., [15,16]). To gain a better understanding of magmatism associated with enigmatic non-plume intraplate settings it is essential to provide petrogenetic constraints on the nature of mantle sources and melts in these settings.…”
Section: Introductionmentioning
confidence: 99%